A temperature difference recorder - VERNEKAR, K. G. (MAUSAM, 1971)
A simple and sensitive instrument for continuously recording difference of temperature between any two levels in the free atmosphere in connection with study of exchange processes in the lower atmosphere has been described. It operates over a temperature range of .0-50 C and has a sensitivity of the order of 0.02°C for temperature difference. Bead thermistors of 1.2 mm diameter are used as sensors after and linearisation of their characteristics.